Saving America's beaches the causes of and solutions to beach erosion - Douglass, Scott L. (Advanced series on ocean engineering, 2002)
This text examines where beach sand comes from, how waves are formed and how they break and move sand down the coast, how "works of man" have blocked this movement and caused beach erosion, and what can be done to save the beaches for future generations of Americans.